Boosting CO tolerance and stability of Pt electrocatalyst supported on sulfonated carbon nanotubes. (12th November 2019) - Luo, Fang; Guo, Long; Zhang, Quan; Ling, Ying; Yang, Zehui; Grigoriev, Sergey A.; Cheng, Hansong
Abstract: CO tolerance and stability are of prominent importance for the anodic electrocatalyst utilized in direct methanol fuel cells (DMFCs). Due to the electrochemical instability of Ru atoms, the state-of-the-art DMFC anodic electrocatalyst (PtRu/C) is unable to survive for long time. Here, we report a newly designed Pt electrocatalyst with robust CO tolerance and stability after coating with poly(vinyl pyrrolidone) (PVP). Electrochemically active surface area (ESA) is negligibly affected by the PVP decoration; meanwhile, almost undetectable ESA loss is obtained for the PVP decorated Pt electrocatalyst. However, the ESA degradations for non-decorated and commercial CB/Pt electrocatalysts are found to be 30% and 40%, respectively. The improved stability is ascribed to the strong interaction between PVP and sulfonated carbon nanotubes. Also, the CO tolerance evaluated from the methanol oxidation reaction is ∼3 and 3.5 fold higher compared to non-decorated and commercial CB/Pt electrocatalysts, respectively, which is attributed to the hydrophilic PVP polymer accelerating the water absorption and formation of Pt(OH)ads species to re-activate nearby CO poisoned Pt nanoparticles. Thus, decoration with PVP polymer can simultaneously promote the stability and CO anti-poisoning of Pt electrocatalyst. Graphical abstract: Image 1 Highlights: Robust CO tolerance is achieved after coating Pt catalyst with hydrophilic polymer. More Pt(OH)ads species is generated after coating with hydrophilic polymer. Pt nanoparticles migration is decelerated by poly(vinyl pyrrolidone) layer.